2021
DOI: 10.1016/j.sdentj.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The state of Oral Medicine and Oral Pathology in the Arab Middle East

Abstract: The Arab World consists of 22 countries with more than half located in the Arab Middle East. Whereas the current state of Oral Medicine and Oral Pathology in the Western World is well known, available information on the current state of Oral Medicine and Oral Pathology across the Arab Middle East is lacking. This concise communication sheds light on the current state of these two specialties with specific reference to specialty training programs, board certification, and future directions. This piece provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Additionally, health care practitioners, including dentists, implemented virtual consultations and communication applications to address patients' chief complaints [23]. Due to a shortage of oral medicine specialists, Saudi Arabia was one country that started using tele-oral medicine even prior to the COVID-19 pandemic to address this demand and patients' needs [8,9]. However, the demand has increased since, as reported by 16.3% of the study participants, and has reached maximum capacity at each health care institute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, health care practitioners, including dentists, implemented virtual consultations and communication applications to address patients' chief complaints [23]. Due to a shortage of oral medicine specialists, Saudi Arabia was one country that started using tele-oral medicine even prior to the COVID-19 pandemic to address this demand and patients' needs [8,9]. However, the demand has increased since, as reported by 16.3% of the study participants, and has reached maximum capacity at each health care institute.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shortage of oral medicine specialists in Saudi Arabia, this study aims to evaluate the utility and effectiveness of tele-oral medicine, focusing on its role in addressing the challenges of limited access to oral medicine specialists in various settings, including rural areas. It seeks to assess how tele-oral medicine can aid in the management of oral lesions, facilitate prioritized referrals for critical cases, and enhance the delivery of dental care, ultimately contributing to more efficient and accessible oral healthcare [8][9][10]. This paper pioneers the simulation of real clinical oral medicine consultation scenarios, considering selected cases to cover all possible aspects, including patients taking images.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Alrashdan et al [34], it was found that senior dental students from a single Jordanian institution demonstrated a lack of interest in postgraduate oral medicine training. This study highlights a greater trend: there are very few established training programs in oral medicine and a lack of career guidance regarding oral medicine opportunities, thus affecting the desire of dental graduates to pursue this field [35]. Training in oral medicine allows graduates to practice in a range of environments, from a medical center to an educational facility to private practice [3].…”
Section: Oral Medicine Residency Programsmentioning
confidence: 99%
“…Training in oral medicine allows graduates to practice in a range of environments, from a medical center to an educational facility to private practice [3]. In response to the higher demand for oral medicine specialists and the potential graduate interest, dental schools should emphasize oral medicine as a viable career path to upcoming graduates and provide them with information on these opportunities [35]. In Saudi Arabia, nevertheless, the number of new graduates who are interested in the field is experiencing a notable increase [18].…”
Section: Oral Medicine Residency Programsmentioning
confidence: 99%
See 1 more Smart Citation